МИЛЛИЙ КУРАШ ОРҚАЛИ ЁШЛАРДА МАЪНАВИЙ ҚАДРИЯТЛАРНИ ШАКЛЛАНТИРИШ ОМИЛЛАРИ - Еримбетов, Б.К. (SCIENCE and SOCIETY, 2016)
The article is devoted to the analysis of the process of forming in the youth spiritual values by means of national fight. The importance of national fight in spiritual education of the youth has been proved from the scientific point of view. The fight is considered as the factor, serving to strengthening of national features.
Keywords: physical training and sports; health; national struggle; national features; national pride; development; education